Factors associated with iron deficiency in heart failure - M. P. Smirnova; P. A. Chizhov (Кардиоваскулярная терапия и профилактика)
Aim. To establish the factors associated with iron deficiency (ID) in pa- tients with heart failure (HF).Material and methods. We examined 294 patients with NYHA class II-IV HF as follows: 213 — with ID, 81 — without ID. All patients underwent a clinical examination, collection of medical history taking into account the presence, duration and severity of comorbidities, drug history, echocardiography, complete blood count, serum iron, ferritin, transferrin, transferrin saturation, soluble transferrin receptors, hepcidin, erythropoietin, and routine laboratory tests. In addition, we determined the presence and severity of asthenia, anxiety, and depression.Results. Twenty-nine clinical, laboratory and echocardiographic parameters were established, which had significant differences in patients with and without ID and significant correlations with ID. Determining the odds ratio for these 29 parameters revealed 7 factors significantly associated with ID in patients with HF. Using multivariate logistic regression, a significant cumulative effect of these factors on the ID risk was established.Conclusion. ID in patients with HF is associated with age, class II-IV HF, elevated hepcidin levels, duration of hypertension and diabetes, history of using angiotensin-converting enzyme inhibitors and novel oral anticoagulants for >1 year.